Socialization of Fermentation Technology on Eco Enzymes as Raw Materials for Agro-industry at Muhammadiyah 3 Jember Senior High School - Fitriana Dina Rizkina; Hudaini Hasbi; Ahib Assadam; Nurul Fathiyah Fauzi; Astri Widyaruli Anggraeni; Tiara Aprilia Hapsari P.P.; Shinta Artamevia Ramad (LPPM UIKA Bogor, 2023)
Waste is a daily problem for human life in the world, this is because waste production occurs every day. The increase in the amount of waste per day causes various diseases that will have a more dangerous health impact on both humans and the environment for the next generation. A clean and healthy school environment will support a good teaching and learning process. Muhammadiyah 3 Jember Senior High School is one of the schools that is always developing to become a model school in Jember Regency. However, based on the results of preliminary observations, organic waste management has not been implemented. Eco enzymes are natural multi-purpose liquids, which are fermented from sugar, fruit/vegetable residues, and water. Eco enzymes can be liquids that provide many benefits for households, agriculture, and animal husbandry. Basically, Eco enzymes accelerate biochemical reactions in nature to produce useful enzymes using fruit or vegetable waste. This enzyme from